Stå på, ikke gi opp – the use of Norwegian particle verbs in email messages by advanced L2 users whose L1 is Finnish - Lieri Kristiina (Finland, 2022)
The aim of the present study is to examine similarities and differences in the use of particle verbs (PVs) between advanced bilingual L2 users of Norwegian (L1 Finnish) in their teens and Norwegian L1 speakers of the same age. The data consists of three writing tasks (email messages) written by 6 bilingual Finnish-Norwegian participants and 6 native speakers of Norwegian. Previous research has shown that second language (L2) users, who are highly advanced, face problems using multi-word expressions. For example, they tend to use less PVs than native speakers. The advanced bilingual L2 users of Norwegian (L1 Finnish) in the present study also show a slight tendency to use fewer PVs than the native speakers. However, the Finnish-Norwegian participants used some more idiomatic PVs than the native speakers of Norwegian. The results show that advanced bilingual users of Norwegian who live in an L2 environment and receive a great amount of natural input and output from an early age utilized PVs in a manner congruent to native speakers. Despite differences between the Finnish and Norwegian languages, there are also similarities with regard to PVs. The bilingual participants are familiar with PVs in their first language, Finnish, and they may benefit from that, even though these verbs are not as frequent in Finnish as in Norwegian.
Keywords:                  Norwegian, particle verbs, advanced L2 users of Norwegian